Integration of Jambi Malay Wisdom and Islamic Values in Sex Education for Early Childhood: A Phenomenological Study of Early Childhood Ed-ucation Teachers - Bangsawan, Indra; Nazurty, Nazurty; Fortunasari, Fortunasari; Anggraini, Ririn; Antonio, Marites Del Prado (POTENSIA: Jurnal Kependidikan Islam, 2026)
This qualitative study aims to identify and analyze how Early Childhood Education teachers in Jambi construct meanings and implement early childhood sex education through Jambi Malay local wisdom and Islamic values. Sex education for young children is positioned as a preventive, value-based effort to protect children from sexual violence while helping them develop developmentally appropriate understandings of the body and personal boundaries. A qualitative design focusing on teachers’ perceptions is used to capture their interpretations and practical considerations in delivering sexuality-related learning within PAUD settings grounded in culture and religion. This approach aligns with previous studies on PAUD educators’ knowledge and attitudes toward early childhood sex education, which emphasize the importance of teacher parent communication and sociocultural mediation in implementation. Data were collected from four teachers purposively selected from two PAUD institutions in Jambi and were analyzed thematically to build interpretive patterns, consistent with research that treats teachers’ perspectives as key to understanding how sex education is delivered and received in Islamic preschool contexts. The analysis produced two main findings: (1) teachers frame early childhood sex education as urgent for child protection and moral formation, interpreting modesty, privacy, and the principle of “adat bersendi syarak” (custom founded upon Islamic law) as a dynamic framework for age-appropriate learning, and (2) teachers operationalize this meaning through culturally relevant, child-friendly strategies such as storytelling, play-based learning routines, and habituation of boundary-setting. These findings indicate that values and norms are socialized through everyday practices and that culturally rooted media and traditional games can function as effective pedagogical vehicles in Early Childhood Education. The study implies that strengthening culturally responsive teacher competence and structured collaboration with parents is necessary to reduce misconceptions, improve message consistency, and sustain preventive impact.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//